Yahweh, the Bad Shepherd? Defamiliarization and Pastoral Symbolism in Zechariah 11:7-17. (August 2015) - Tran, Quang D.
Defamiliarization is transformative exegesis. More than a search for meaning, the process of defamiliarization attempts to revitalize scriptural symbolism and let symbols do what they do, namely, to push back, refusing to be pinned down and mediating an ongoing, transformative relationship that can always go deeper. When Scripture is defamiliarized, Scripture defamiliarizes, resulting in a revitalization of certain symbols that facilitate a life-giving exchange between text and reader especially for personal prayer and preaching that enriches the community of faith. In this essay, I will explore the application of this thesis to Zechariah 11:4-17, a most enigmatic passage. Analysis of the pastoral symbolism and its rhetorical function in this passage reveals how the process of defamiliarization revitalizes biblical pastoral symbolism. Since God is dynamic, the symbols that represent him should be dynamic. No symbol reveals the whole truth, but the possibilities to reveal different aspects of the same truth can be limitless.